Description of a new genus and species of Encyrtidae (Hymenoptera: Chalcidoidea) from Danish amber, based on a male specimen featuring an antenna with a distinct anellus - Simutnik, Serguei A.; Perkovsky, Evgeny E. (Zootaxa, 2023)
Electroanellus belokobylskiji Simutnik gen. et sp. nov. (Hymenoptera: Encyrtidae) is described and illustrated based on a male specimen from late Eocene Danish amber. The presence of an anellus between the pedicel and the first funicular segment is the main difference between the new taxon and most extant encyrtids, as well as all described fossil species. The new fossil also differs from all known Eocene Encyrtidae by its relatively short marginal vein, which is as long as broad. The placement of the new genus in the subfamily Tetracneminae is supported by the absence of the filum spinosum of the linea calva.